2010
DOI: 10.1103/physrevb.82.144116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation parameters on defect aggregation during thermal annealing of LiF irradiated with swift ions and electrons

Abstract: Absorption spectroscopy were performed to study the effects of thermal annealing on the aggregation of color centers in LiF crystals irradiated with different ions between carbon and uranium of megaelectron volt-gigaelectron volt energy. The beam parameters such as energy, energy loss, and fluence have a pronounced influence on the initial defect composition and concentration as well as their evolution upon thermal annealing. A distinct phenomenon was observed, viz., the enhancement of F n centers for annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…High quality LiF crystals grown from the melt in inert atmosphere (Korth Kristalle, Germany) were used in the experiments (see Ref. 15, 16 for details). X‐ray luminescence analysis detected Mg (20 ppm), Na (1 ppm), and Cl (1 ppm) trace elements in these crystals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…High quality LiF crystals grown from the melt in inert atmosphere (Korth Kristalle, Germany) were used in the experiments (see Ref. 15, 16 for details). X‐ray luminescence analysis detected Mg (20 ppm), Na (1 ppm), and Cl (1 ppm) trace elements in these crystals.…”
Section: Methodsmentioning
confidence: 99%
“…The thicknesses of all samples were larger than the ranges of applied ions 17. In addition to the room temperature irradiations, some samples were irradiated at 8 K in a cryostat installed in the beam line 15, 16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stability of various defects in LiF irradiated with heavy ions depends on the ion energy loss and fluence [19]. During thermal annealing two different processes take place: (1) the decomposition of V 3 centers with H center production; (2) diffusion of single F centers with the following formation of complex electron color centers according to the reactions F + F n ?…”
Section: Thermal Annealingmentioning
confidence: 99%
“…The lower energy could explain the defect stability under illumination with the red (1.96 eV) laser. Also, such processes had already been proposed for LiF samples thermally annealed after ion or electron irradiation . As the temperatures were increased in this study, it was shown that the annihilation of single centers first occurred (below 500 K), followed by the aggregation of more complex center (500–600 K) and the formation of larger Li colloidal particles (600–700 K), culminating into their reduction/disappearance (above 700 K).…”
Section: Resultsmentioning
confidence: 99%